The Chinese Development Model and The Multi-Polar World. Exploring the Possibility of Other Countries Adapting and Adopting This Model - FLORIN BONCIU (Global Economic Observer)
The development results achieved by China in the past 30 years are so impressive and evident that they can be neither ignored nor denied. As a result, in many developing and even developed countries there is an interest for understanding what are the characteristics of the Chinese development model, whether there are any prerequisites and what are the costs. The paper analyzes the merits of this model and particularly its effectiveness in achieving tangible results in the development process and particularly in moving from quantitative to qualitative results. The conclusion is that particularly for the developing countries the Chinese development model may become more attractive towards the middle of the 21st century.